Development of IR-mediated thermocycling system and multi-reaction PCR chip for DNA amplification - Tan, Yin (2008)
[THIS THESIS CONSISTS OF TWO (2) PARTS - THIS IS PART 1]. The applications and development of polymerase chain reaction (PCR) for DNA analysis is becoming important in molecular diagnostics and drug development. Many conventional PCR systems use glass or plastic based tubes with relatively big volumes (>25mL) to conduct PCR. Thus, this resulted in more reagents consumed and longer reaction time to reach thermal balance because their larger volume tubes and slow thermal cycling. With the applications of MEMS technologies, PCR microship can be realised. These PCR microdevices can greatly reduce the DNA analysis cost with less consumption of reagent and offers the potential of rapid thermal cycling. The present work is aimed to design, analyse and fabricate a multi-reaction PCR chip and PCR thermocycler for DNA amplification. The chip will consist of multiple reaction vessels for high throughput PCR. The thermocycler will perform heating processes by infra-red (IR) radiation, and cooling process by forced convection. In addition, the thermocycler is capable of on-board real-time PCR products detection.